PENGARUH STATUS SOSIAL EKONOMI ORANG TUA DAN KOMPETENSI GURU TERHADAP KOMPETENSI VOKASIONAL SISWA - Sarofah, Sarofah; Witarsa, Witarsa; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study is to examine how much influence parents' socioeconomic status and teacher competence on vocational competence of students majoring in marketing SMK Negeri 8 Pontianak. The data collected in this study were analyzed using quantitative analysis using descriptive methods. The population of this study were 52 students of SMK Negeri 8 Pontianak by taking all the population as a sample. While the tools in this study were questionnaires/ questionnaires that had been validated and reliability, interviews and documentary studies. From the results of this study,Â  it is known that there is an influence between two independent variables on the dependent variable it was 28%.Â Keywords: Socio-Economic Status of Parents, Teachers Competency and StudentsVocational Competency.